2021
DOI: 10.1016/j.jbi.2021.103920
|View full text |Cite
|
Sign up to set email alerts
|

A novel deep interval type-2 fuzzy LSTM (DIT2FLSTM) model applied to COVID-19 pandemic time-series prediction

Abstract: Currently, the novel COVID-19 coronavirus has been widely spread as a global pandemic. The COVID-19 pandemic has a major influence on human life, healthcare systems, and the economy. There are a large number of methods available for predicting the incidence of the virus. A complex and non-stationary problem such as the COVID-19 pandemic is characterized by high levels of uncertainty in its behavior during the pandemic time. The fuzzy logic, especially Type-2 Fuzzy Logic, is a robust and capable model to cope w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Long short-term memory (LSTM), the most representative one of deep-learning, is a special kind of RNN, which is mainly designed to solve the gradient disappearance and gradient explosion problems during the training of long sequences. LSTM has been proved to be a powerful deep-learning network for the forecast of COVID-19 infections [ [40] , [41] , [42] , [43] ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Long short-term memory (LSTM), the most representative one of deep-learning, is a special kind of RNN, which is mainly designed to solve the gradient disappearance and gradient explosion problems during the training of long sequences. LSTM has been proved to be a powerful deep-learning network for the forecast of COVID-19 infections [ [40] , [41] , [42] , [43] ].…”
Section: Literature Reviewmentioning
confidence: 99%
“… USA, Brazil, etc. [ 41 ] generalized linear and tree-based machine learning models 0.21 N.P. 0.99 N.P.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Methods for short-term forecasting are usually data-driven, but they can also incorporate domain knowledge in the form of compartmental modelling (i.e., SIR-type models – see [48] ), as a means of integrating and simultaneously forecasting in a coherent manner multiple epidemiological indicators, such as cases, hospitalizations, and deaths. The study by Swaraj et al [21] uses a statistical data-driven approach, Aljaaf et al [22] , Dairi et al [23] , and Safari et al [24] use a machine learning data-driven approach, while Jing et al [25] uses compartmental modelling. Most of the forecasting studies were conducted as stand-alone evaluations or comparisons of methods by researchers who were not directly affiliated with public health authorities mandated to perform surveillance.…”
Section: Forecasting and Epidemic Modelingmentioning
confidence: 99%
“…Most of the forecasting studies were conducted as stand-alone evaluations or comparisons of methods by researchers who were not directly affiliated with public health authorities mandated to perform surveillance. In terms of epidemiological indicators being forecast, the studies focused on confirmed cases, hospitalizations and deaths, although the contribution of smartphone mapping data, was explored by Jing et al [25] Methodologically, most studies used statistical and ML methods, either in comparison (Dairi et al [23] and Safari et al [24] ), within an ensemble (Aljaaf et al [22] and Swaraj et al [21] ), or as a part of a pipeline. Although results varied, findings were consistent with a recent review of methods for aberration detection in public health, with ML methods tending to outperform statistical methods for short-term forecasting.…”
Section: Forecasting and Epidemic Modelingmentioning
confidence: 99%
See 1 more Smart Citation